PROPOSED AMENDMENTS TO THE OPERATIONAL ACTIVITIES LAW ENDORSED BY PARLIAMENTARY SUBCOMMITTEE - Ivančiks, Jānis (Administrative and Criminal Justice, 2015)
The article provides insight into the actual problem of law enforcement authorities – amendments and supplements on Operational activities Law. The article also gives analysis of proposals of amendments and supplements given by Subcommittee of Parliamentary Defense, Internal Affairs and Corruption Prevention Committee. Simultaneously author takes into account realistic circumstances, situations and opportunities of operational structures and exigency of respecting for human rights and gives certain proposals how to resolve identified problems.